PUBLIC KNOWLEDGE, PRACTICES AND ATTITUDES TOWARDS COVID-19 IN AFGHANISTAN - Orfan, Sayeed Naqibullah; Elmyar, Abdul Hamid (Public Health of Indonesia, 2020)
Background: COVID-19 has tremendously affected the world including Afghanistan since its outbreak.Objective: This study aimed to investigate the public knowledge about COVID-19 in Afghanistan as well as practices used to prevent contracting the disease. It also studied the attitudes of the public towards the COVID-19 survivors, and the impact of the participants' gender, place of residence and marital status on their responses.Method: The data were collected from 1472 individuals through an online survey questionnaire. SPSS version 24.0 was used to analyze the data.Results: The findings showed that the public were very knowledgeable about COVID-19. They used various practices to varying extent to prevent contracting COVID-19 and its spread. Moreover, the participants' attitudes towards the COVID-19 survivors varied. They had negative attitudes towards them if close contact was concerned, but their attitudes were positive towards them if close contact was not involved, e.g., educating community members about the disease. Gender and place of residence had a significant impact on the participants' knowledge and practices, but they did not affect their attitudes towards the survivors. Furthermore, marital status significantly affected the participants' practices, but it did not have any impact on their knowledge and attitudes towards the survivors.